Fatigue Factors among Thai Airways Cabin Crew: A Proactive Management Approach under the Thailand Civil Aviation Regulation (TCAR) - Sangsuk, Nuchareeya (KBU Journal of Aviation Management:KBUJAM, 2026)
Proactive Safety Management Innovation: Analyzing Fatigue Factors among Thai Airways Cabin Crew in Compliance with the Thailand Civil Aviation Regulation (TCAR) This study investigates the factors contributing to fatigue among flight attendants of Thai Airways International Public Company Limited, with a focus on compliance with the Civil Aviation Authority of Thailand (CAAT) regulations on Flight and Duty Time Limitations (FTL). A qualitative research approach was employed, utilizing semi-structured interviews with executives, aviation experts, and flight attendants. The findings indicate that prolonged Flight Duty Periods significantly contribute to fatigue by disrupting circadian rhythms, particularly when duties coincide with the Window of Circadian Low. Moreover, the working environment and rapid turnarounds exacerbate fatigue by reducing sleep quality, even when duty hours are within legal limits. These results highlight the importance of implementing a Fatigue Risk Management System (FRMS), representing a transition from reactive regulatory compliance to proactive, science-based fatigue management. Integrating FRMS with the promotion of a Just Culture enhances aviation safety and supports sustainable well-being among aviation personnel, aligning with international standards in modern aviation operations. Keywords: Safety Management Innovation, Fatigue, Thailand Civil Aviation Regulation: TCAR, Flight Time Limitations: FTL, Fatigue Risk Management System: FRMS *Corresponding Author: Email: nuchareeya37379@gmail.com